The Effect of The Implementation of Worksheet Based-Problem Solving on Students’ Critical Thinking Skills in Rotational Dynamics and Elasticity - Vanessa Febta Sindani; Yenni Darvina; Ramli Ramli; Wahyuni Satria Dewi (Universitas Negeri Padang, 2020)
The purpose of the research was to investigate the effect of worksheet based-problem solving on students' critical thinking skills in rotational dynamics and elasticity . The research design used is posttest-only. The study involved two sample classes: the experiment class and the control class. Data collection techniques in the form of written tests with a model of description questions. The assessment is based on indicators of critical thinking skills that can be observed The results of the study show by applying the same learning model that is the problem-solving learning model, it can be said that both sample classes occurred an increase in the value of critical thinking skills. However, the critical thinking skills of each indicator are higher indicators of analysis, evaluation, and inference in the experiment class compared to the control class, and the average increase in students' grades is seen from final exam scores and the final test scores of the study in the experiment class are higher than the control class. This means that worksheet based-problem solving is instrumental in improving students' critical thinking skills in rotational dynamics and elasticity materials in Grade XI of High School in Kerinci.